THE TRAFFIC ANALYSIS ON THE SIGNALED T-JUNCTION (A Case Study Of Purwokerto Indah (Purin) T-Junction, Kendal) - Dwi Wahyu Hidayat (International Conference on Coastal and Delta Areas, 2017)
Purwokerto Indah T-Junction (Purin) is one of the T-Junctions located in the district of Kendal. This place is found to be a signaled T-Junction and belongs to education and housing area. Looking at its function, it connects Jl. Tentara Pelajar with Jl. Soekarno-Hatta, the main road of North Beach (Pantura). In the rush hours, especially in the Morning and in the Afternoon, this site becomes crowded and vulnerable to conflict due to being located on the area of Jl. Soekarno-Hatta, the main road of North Beach (Pantura). In order to meet the need of this research, surveys on the flow of traffic, type of vehicle, Geometry of road, and phase of traffic on the T-Junction were conducted. These surveys were made on Sundays, Mondays and Wednesdays at 06.00 to 18.00. The T-Junction performance analyses were made by referring to MKJI where it included the level parameter of saturation, postponement, and T-Junction services. Of the data analyses, the intersection performance values at the peak condition were found to be at the south area of Jl. Tentara Pelajar with the level of saturation (DS) 0.937, and the total of delay 61.827 seconds/unit of passenger car that it belonged to service level D. For the west area of Jl. Soekarno-Hatta, this had the level of saturation (DS) 0.937, and the total of delay 57.528 seconds/unit of passenger car, where this belonged to level D in term of service. For the east area of Jl. Soekarno-Hatta, the level of saturation (DS) was 0.937, and the total of delay was 80.374 seconds/unit of passenger car. It means, the average of intersection delay in the T-junction, Purin, Kendal was 34.27 seconds. This further explains that the service level of Purwokerto Indah (Purin) T-Junction, Kendal belonged to level D. Keywords : MKJI; Signaled T-junction, Service Level